Situasi Disabilitas Di Dunia Pekerjaan - Dea Pitaloca; Hafizhah Nurkhalishah; Nida Nur Azizah P; Rifa Aulia Dienan M; Siti Hamidah (Universitas Maritim AMNI Semarang, 2023)
In the work world everyone is entitled to his right to work, as are the disabled. According to 2016's law no. 8, which states that private companies are required to employ at least 1% (one percent) of the disability from the number of employees or workers. Before people with disability get a job or an expert in their field of work, they have to acquire programs from their school of vocational programs. The vocational program isa program to develop their self-reliance and skills consistent with that of children with disabilities. Skills developed within a child's potential can provide a child with the ability to determine where he or she will continue. Will continue to be a student or will work within the potential of children in high school. The purpose of this study is to identify the situation of disability in the work world where we use qualitative methods. Meanwhile, his data collection techniques are through interviews and observations to one of the professors of the special education study program, slb-c yplb cipaganti and SLB country of cileunyi. In the study found that children with disabilities get their votive activities while in high school and some of those with lightweight categories of inhibitions, they can continue to work within their potential and parental support or assistance.